Risk factors for cardiovascular multimorbidity in UK women - Suh, JW (2022)
Background: Multimorbidity is the presence of two or more chronic diseases in one person, and in this thesis, cardiovascular multimorbidity (CVM) refers to the co-occurrence of two or more cardiovascular disease subtypes. Multimorbidity is a major public health concern in the UK and CVM is a key component. However, there is currently limited large-scale, prospective evidence on risk factors for CVM.